MixInYeast: A Multicenter Study on Mixed Yeast Infections - Medina, Narda; Soto-Debran, Juan Carlos; Seidel, Danila; Akyar, Isin; Badali, Hamid; Barac, Aleksandra; Bretagne, Stephane; Cag, Yasemin; Cassagne, Carole; Castro, Carmen; Chakrabarti, Arunaloke; Dannaoui, Eric; et al. (MDPI, 2021)
Invasive candidiasis remains one of the most prevalent systemic mycoses, and several studies have documented the presence of mixed yeast (MY) infections. Here, we describe the epidemiology, clinical, and microbiological characteristics of MY infections causing invasive candidiasis in a multicenter prospective study. Thirty-four centers from 14 countries participated. Samples were collected in each center between April to September 2018, and they were sent to a reference center to confirm identification by sequencing methods and to perform antifungal susceptibility testing, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST). A total of 6895 yeast cultures were identified and MY occurred in 150 cases (2.2\%). Europe accounted for the highest number of centers, with an overall MY rate of 4.2\% (118 out of 2840 yeast cultures). Of 122 MY cases, the most frequent combinations were Candida albicans/C. glabrata (42, 34.4\%), C. albicans/C. parapsilosis (17, 14\%), and C. glabrata/C. tropicalis (8, 6.5\%). All Candida isolates were susceptible to amphotericin B, 6.4\% were fluconazole-resistant, and two isolates (1.6\%) were echinocandin-resistant. Accurate identification of the species involved in MY infections is essential to guide treatment decisions.
Keywords: yeast; chrome agar; invasive candidiasis; Candida; mix infections; polymicrobial infections